A new chaotic model for glucose-insulin regulatory system. (July 2018) - Shabestari, Payam Sadeghi; Panahi, Shirin; Hatef, Boshra; Jafari, Sajad; Sprott, Julien C.
Highlights: A new model for insulin-glucose regulatory system is proposed. This model is based on the well-known prey and predator models. This model is in accordance with previous experimental studies. One interesting feature of this new model is having hidden attractor. Abstract: For non-invasively investigating the interaction between insulin and glucose, mathematical modeling is very helpful. In this paper, we propose a new model for insulin-glucose regulatory system based on the well-known prey and predator models. The results of previous researches demonstrate that chaos is a common feature in complex biological systems. Our results are in accordance with previous studies and indicate that glucose-insulin regulatory system has various dynamics in different conditions. One interesting feature of this new model is having hidden attractor for some set of parameters. The result of this paper might be helpful for better understanding of regulatory system that contains glucose, insulin, and diseases such as diabetes, hypoglycemia, and hyperinsulinemia.